Posner-Schlossman Syndrome (Glaucomatocyclitic Crisis) A 5-Year Review - Emma Rusmayani (Majalah Oftalmologi Indonesia, 2021)
Background: Posner-Schlossman syndrome (PSS) or glaucomatocyclitic crisis is a rare condition with self-limited unilateral recurrent episodes of elevated intraocular pressure (IOP) and mild anterior chamber inflammation in which diagnosis can be challenging. We reviewed our 5-year experience with PSS to give a brief picture of the natural characteristic of the disease. Methods: We investigated 56 eyes from 52 patients (24 males and 28 females; both eyes for 2 males and 2 females) diagnosed with PSS during the years 2012-2017 in the Jakarta Eye Center Menteng and Kedoya. Data were collected on age, gender, visual acuity, episode of attacks, drugs regimen, IOP during attacks and after surgery or treatment in the latest follow up. Results: The mean age of the 52 patients was 48.13 years-old (range, 18–82 years). The mean intraocular pressure (IOP) of initial record for all 56 eyes was 37.63 mmHg (ranged from 10-65 mmHg). The mean visual acuity during attacks was 0.87 LogMAR and mean episode of attacks was 2.41 times, with 41% of the cases were their first time onset. Medical treatment was efficacious for 39 patients (69.62 %). Eight patients (14.82 %) underwent a surgical treatment and all had normal IOP afterwards. Conclusions: PSS was found more in middle-aged patients. PSS tend to be the typical self-limiting and response well to medical treatment. However, the episodic and recurrent nature of PSS should be a concern. Therefore, patients with PSS must have regular evaluation of visual acuity, visual fields and IOP.